2017
DOI: 10.1002/jcp.26251
|View full text |Cite
|
Sign up to set email alerts
|

A high throughput method to study the physiology of E2:ERα signaling in breast cancer cells

Abstract: 17β-estradiol (E2) regulates diverse physiological effects including cell proliferation through the estrogen receptor α (ERα), which as a transcription factor drives gene transcription and as an extra-nuclear localized receptor triggers the membrane-dependent activation of diverse kinase cascades. E2 also modifies ERα intracellular levels via diverse intracellular mechanisms. In this way, the E2-acivated ERα integrates signaling cascades with the modulation of receptor intracellular concentration and with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 42 publications
(94 reference statements)
1
46
0
Order By: Relevance
“…ERα is critical to the development of ER+ breast cancer, 84 which accounts for approximately 70% of all breast cancers. 7,85 Overexpression of ERα frequently sensitizes tumors to endocrine therapy. 84 When exposed to E2, ERα activation stimulates downstream signaling pathways, 86 and leads to EMT and ECM remodeling (Figure 3).…”
Section: Erα and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…ERα is critical to the development of ER+ breast cancer, 84 which accounts for approximately 70% of all breast cancers. 7,85 Overexpression of ERα frequently sensitizes tumors to endocrine therapy. 84 When exposed to E2, ERα activation stimulates downstream signaling pathways, 86 and leads to EMT and ECM remodeling (Figure 3).…”
Section: Erα and Cancermentioning
confidence: 99%
“…ERs can be activated when cells are exposed to estrogen. [7][8][9] Emerging evidence shows that the activation of ERs is highly associated with cancer formation and metastasis, [10][11][12] extracellular matrix (ECM) remodeling 2,13 and drug resistance. [14][15][16][17] Here, we focus on providing a comprehensive understanding of ERα.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, different strategies are being used to identify novel BC treatments [ 14 ]. Our research group has recently introduced the concept of targeting the selective modulation of ERα levels as a promising approach to discover new anti-BC compounds [ 14 , 59 , 60 , 61 ]. We have indeed demonstrated that drugs that do not necessarily bind to ERα but instead change the amount of ERα protein in BC cells can prevent BC cell proliferation and subsequent tumor growth [ 14 ].…”
Section: The Ras Endocrine System In Cancermentioning
confidence: 99%
“…We have indeed demonstrated that drugs that do not necessarily bind to ERα but instead change the amount of ERα protein in BC cells can prevent BC cell proliferation and subsequent tumor growth [ 14 ]. In turn, we demonstrated this by screening a library of 1018 Food and Drug Administration (FDA)-approved drugs in BC cells to search for molecules that modify ERα content and prevent BC cell growth [ 14 , 59 , 61 , 62 ]. This line of research led to the discovery that more than 50 FDA-approved compounds affected ERα content in MCF-7 cells and, among them, 11 also inhibited cell proliferation [ 59 ].…”
Section: The Ras Endocrine System In Cancermentioning
confidence: 99%
See 1 more Smart Citation